â€œSTANDARDIZATION OF BHALLATAK AVALEHAâ€: Array - Shende, Harshal Janardan (Ayurline: International Journal of Research in Indian Medicine, 2020)
Ayurveda is the holistic science of life. In ancient scriptures of Ayurveda, medicinal properties of Bhallatak has been described. Bhallatak is acclaimed as a drug of choice in the treatment of piles of vata and kapha types. Avaleha is the most common secondary Kalpana which has been employed in various disorders and this product is gaining popularity due to its easy administration, palatability and longer shelf life. Bhallatak Avaleha is a Leha kalpana mentioned in Bhaishajya Ratnavali arsha rogadhikar adhyaya. Bhallatak Avaleha is useful in all age groups. It is a multipurpose Ayurveda formulation mainly used in all sorts of diseases. It is also beneficial in various upper respiratory tract diseases like kaas, shwaas etc. Acharyas mention Bhallatak Avaleha as the best rasayna drug. 3 batches were prepared and analytical study was done.